2020
DOI: 10.1021/acsabm.0c00626
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Near-Infrared Image Assessment of Surface-Acetylated Solid Wood

Abstract: Visualization of acetic anhydride flow and its heterogeneity within the wood block necessitates the development of a reliable and robust analytical method. Hyperspectral imaging has the potential to acquire a continuous spectrum of chemical analytes at different spectral channels in terms of pixels. The large set of chemical data (3-dimensional) can be expanded into relevant information in a multivariate fashion. We quantified gradients in acetylation degree over cross sections of Scots pine sapwood caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…This indicates that the rate of acetic anhydride diffusion into the cell walls of earlywood and latewood was similar, but since earlywood has thinner cell walls than latewood, a higher proportion of earlywood cell walls was acetylated compared to latewood cell walls when subjected to the same treatment time. This has also been observed in recent studies (Awais et al 2020;Mäkelä et al 2021). Consequently, for interface modification of the highest degree, the diffusion fronts from adjacent earlywood cells often reached all the way to their common middle lamella, leading to its acetylation (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…This indicates that the rate of acetic anhydride diffusion into the cell walls of earlywood and latewood was similar, but since earlywood has thinner cell walls than latewood, a higher proportion of earlywood cell walls was acetylated compared to latewood cell walls when subjected to the same treatment time. This has also been observed in recent studies (Awais et al 2020;Mäkelä et al 2021). Consequently, for interface modification of the highest degree, the diffusion fronts from adjacent earlywood cells often reached all the way to their common middle lamella, leading to its acetylation (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…We have recently observed similar differences in the acetylation rate of earlywood and latewood when the acetylation was initiated after a confined, onesided flow of acetic anhydride into the wood [22]. However, earlier studies in the wood field, in which wood samples were completely soaked in acetic anhydride prior to acetylation, have found little to no difference in the WPGs of earlywood and latewood.…”
Section: Discussionmentioning
confidence: 70%
“…We have recently shown that hyperspectral NIR imaging and image regression can successfully determine the penetration of acetic anhydride into the wood structure after wood acetylation [22]. Our method was based on calibrating NIR images with external WPG values measured from dried samples after confined one-sided acetylation of solid wood.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Standard normal variate scaled the data with mean zero and unit standard deviation in a rowwise fashion. Principal component analysis was performed on mosaic following singular value decomposition [12,31] algorithm. Principal components explaining the maximum variation within the data were chosen, and score vectors were reshaped back to image dimensions.…”
Section: Image Calibration and Transformationmentioning
confidence: 99%
“…In this regard, hyperspectral near-infrared (NIR) imaging is an appropriate method to study structural and chemical changes within the wood [10][11][12]. The NIR images are three-way datasets, where two dimensions render the spatial mapping of the chemical analytes, while the third dimension contains spectral variables.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%